Potencial ornamental, propagação, rendimento de óleos essenciais e resposta à deficiência hídrica de ipoméias - Tognon, Grasiela Bruzamarello (2010)
Ipomoea is the largest genus of the family Convolvulaceae. Ipomoea cairica (L.) Sweet and I. purpurea (L.) Roth, are known to be invasive cultures. By are native plants, they adapt very well in climate conditions of the region with characteristics that they allow the use of ornamentation in parks and gardens, but still not popularly cultivated as ornamental, not being cited as marketing products national flower. Moreover, in the case of I. cairica, can play multiple uses within the garden, because display medicinal properties in its composition chemistry. With the following objectives: to study the use and potential ornamental in the morning glories; to evaluate the germination and the force of I. cairica and I. purpurea in different temperatures; to evaluate the response of I. cairica in different water regimes and after the restoration of water regime of vessel capacity; to evaluate the production of essential oils of I. cairica and I. purpurea in different sampling times and drying temperatures, were conducted three studies: 1) sexual propagation of I. cairica and I. purpurea, seeds subjected to different temperatures and after the test accelerated aging to evaluate the force; 2) Asexual propagation, testing the first experiment two types of cuttings and four substrates, and the second were tested five different concentrations of IBA; 3) water stress, testing the response of I. cairica in four water regimes and after the restoration of the system normal water. Seed germination of two morning glories was very low, where the best temperature for germination was 30° C, with seedlings showing a good adaptability to the transplant nursery. Substrates suitable for the propagation cuttings are sand and rice hulls, and rooting percentage and the use of 500 mg L-1 IBA provided better rooting. The time that show increased production of oil was March for the two species. I. cairica showed 100% survival in period of water stress and after the restoration water resumed its growth, showing be a species resistant to drought and may used as an ornamental plant projects landscape in places with low availability water